A Case Report of Lung Adenocarcinoma with EGFR G719A Mutation and LMNA-NTRK1 Fusion - Shiqi SONG; Yaxian YANG; Weiquan LUO; Yueya LIANG; Qi LI; Tongxu ZHUO; Weibin XIONG; Jian HUANG (Chinese Journal of Lung Cancer)
Fusion variations of neurotrophic receptor tyrosine kinase (NTRK) are oncogenic drivers in various solid tumors such as breast cancer, salivary gland carcinoma, infant fibrosarcoma, etc. Gene rearrangements involving NTRK1/2/3 lead to constitutive activation of the tropomyosin receptor kinase (TRK) domain, and the expressed fusion proteins drive tumor growth and survival. NTRK fusions are estimated to occur at a frequency of approximately 0.1% to 1% in non-small cell lung cancer (NSCLC). Epidermal growth factor receptor (EGFR) mutations are prevalent in NSCLC, but the frequency of EGFR G719A mutation is relatively low (about 2%), and EGFR mutations are typically mutually exclusive with NTRK fusion variants. The study presented the first documented case of lung adenocarcinoma harboring both EGFR G719A mutation and LMNA-NTRK1 fusion. A review of the literature was conducted to elucidate the role of NTRK fusion mutations in NSCLC and their relationship with EGFR mutations, aiming to enhance the understanding of NTRK fusion mutations in NSCLC.